Patriotism, nationalism, and evaluations of the government’s handling of the coronavirus crisis - Zhai, Yida; Lu, Yizhen; Wu, Qidi (Frontiers in Psychology, 2023)
The COVID-19 pandemic has been accompanied by a global rise of nationalism, and many countries’ responses to the pandemic have further intensified nationalist sentiments. The public is polarized over government policies toward the pandemic. Hence, we examined the associations of patriotism and nationalism with the support for lockdown policies and evaluations of governmental performance. Patriotism and nationalism had a direct effect on evaluations of governmental performance. They also had indirect effects on favorable evaluations of governmental performance through the support of lockdown policies. In addition, this study examined the relationship of threat perception and evaluations of governmental performance in the pandemic. This relationship was found to be insignificant; however, the interaction effects between threat perception and patriotism on evaluations of governmental performance were significant. The implications of the study results are discussed.